Adorno reader and critic of Husserl: the reformulation of dialectics from the critique of phenomenology - Caires Correia, Fábio; Perius, Oneide (Argumentos - Revista de Filosofia, 2025)
To understand Adorno’s relationship with phenomenology, or rather, the Adorno-Husserl relationship, it is important to distinguish two inseparable moments: (I) the critique of phenomenology operated from the dialectic, and (II) the recognition of the legitimacy of a phenomenological moment against Hegelian idealism. From a conceptual point of view; it is, therefore, a matter of deconstructing the primacy of the former, which characterizes the phenomenological concept of the latter, and then denouncing the idealist claim of a totalization of all mediations in a thought system. The coexistence of these two requirements in the same method could have been reduced, if not to a contradiction, at least to an aporia. The settling of accounts with Husserlian idealism becomes, therefore, prima facie an important reading key for understanding Adorno’s philosophy. Even more so when it comes to the negative form that his dialectic will take. These are the questions that the present paper intends to discuss.